Financial Toxicity After Acute Respiratory Distress Syndrome: A National Qualitative Cohort Study*. Issue 8 (August 2020) - Hauschildt, Katrina E.; Seigworth, Claire; Kamphuis, Lee A.; Hough, Catherine L.; Moss, Marc; McPeake, Joanne M.; Iwashyna, Theodore J.
Abstract : Objectives: The financial burdens and subsequent related distress of medical care, referred to as financial toxicity, may limit access to beneficial treatments. However, financial toxicity after acute care is less described—and may be an important but underexplored mechanism preventing full recovery after critical illnesses such as acute respiratory distress syndrome. We sought to identify the mechanisms by which financial toxicity manifested in patients with acute respiratory distress syndrome, protective factors against such toxicity, and the consequences of financial toxicity to survivors' lives following acute respiratory distress syndrome. Design: We conducted semistructured interviews following patients' hospitalization and during recovery as an ancillary study to a multicenter randomized clinical trial in acute respiratory distress syndrome. Patients were 9–16 months post randomization at the time of interview. Setting and Participants: The Reevaluation Of Systemic Early Neuromuscular Blockade trial examined the use of early neuromuscular blockade in mechanically ventilated patients with moderate/severe acute respiratory distress syndrome. We recruited consecutive surviving patients who were English speaking, consented to follow-up, and were randomized between December 11, 2017, and May 4, 2018 ( n = 79) from 29 U.S. sites. Measurements and Main Results: We asked about patients' perceptions of financial burden(s) that they associated with their acute respiratory distress syndrome hospitalization. Forty-six of 79 eligible acute respiratory distress syndrome survivors (58%) participated (from 22 sites); their median age was 56 (interquartile range 47–62). Thirty-one of 46 reported at least one acute respiratory distress syndrome-related financial impact. Financial toxicity manifested via medical bills, changes in insurance coverage, and loss of employment income. Respondents reported not working prior to acute respiratory distress syndrome, using Medicaid or Medicare, or, conversely, generous work benefits as factors which may have limited financial burdens. Patients reported multiple consequences of acute respiratory distress syndrome–related financial toxicity, including harms to their mental and physical health, increased reliance on others, and specific material hardships. Conclusions: Financial toxicity related to critical illness is common and may limit patients' emotional, physical, and social recovery after acute respiratory distress syndrome hospitalization for at least a year. Abstract : Supplemental Digital Content is available in the text.